ANALISIS NILAI-NILAI EDUKATIF DALAM NOVEL “LOVE IN PESANTREN” SEBAGAI REFORMULASI POLA INTERAKSI GURU DAN MURID DI PESANTREN - Achmat Mubarok; Asrul Anan (Universitas Yudharta Pasuruan, 2019)
Teacher and student interaction is very important in supporting educational success. A good pattern of interaction between teacher and student will create an educational and enjoyable atmosphere. One of the novels by Shachree M. Daroini entitled "Love In Pesantren" is a story of life in pesantren with various patterns of interaction between teacher and student. The educational values ​​contained in the novel "Love In Pesantren" are: the value of faith and devotion, help, enthusiasm to carry out religious rituals, realize self-limitation, be able to accept change, amuse you, self-reliance, the principle of justice, respect and respect fellow human beings, think critically about life, forgive. Things that are less relevant in the pattern of interaction between teachers and students in the pesantren in the novel "Love In Pesantren", among others: giving physical punishment beyond the level of ability, attitude that is not loving, does not respect students, treats students as they wish, does not give opportunity for students to defend themselves, not humanize students, authoritarian attitudes, rely on critical reasoning on the basis of keta'dziman. While the pattern of interaction between teachers and students as a reformulation of interaction in Islamic boarding schools by increasing faith and devotion, gives a great deal of ritual diversity, mutual respect between teachers and students, respect for differences, principles of justice, forgiveness, not feeling right, and mutually open.